Mosquito Control in North Carolina : Funding Issues and Emergency Management - Harris, Jonathan W. (East Carolina University, 2014)
Natural disasters such as hurricanes may cause increases in mosquito abundance and, consequently, arbovirus transmission risk. In 2011, flooding from Hurricane Irene in eastern North Carolina (NC) resulted in increased mosquito populations that hindered recovery efforts. Budget shortfalls in NC have reduced the functionality of long-term mosquito surveillance and control programs; hence, many counties rely on the Federal Emergency Management Agency for post-disaster mosquito control. This pilot study examines mosquito abundance pre- and post-aerial insecticide spraying at eight study sites in Washington and Tyrrell Counties in rural eastern NC after Hurricane Irene. Traps in spray zones show decreases in mosquito abundance following aerial pesticide application compared to control traps, although no significant differences (p > 0.05) were observed. Implications of reactive rather than proactive mosquito control responses are discussed. The absence of state mosquito control funding left some emergency managers (EMs) with the added burden of mosquito control, including coordination, implementation, and reimbursement for control activities. In the second part of the study, surveys were sent to emergency managers in 100 counties in NC to gain a better understanding of the responsibilities EMs face with regard to mosquito control in post-disaster situations. . Results indicate mosquito problems impacted the eastern counties of NC more than the rest of the state, likely due to additional burdens of salt marsh mosquitoes in eastern NC. Additionally, while EMs in eastern NC are confident that local mosquito control programs are capable of handling future disasters, they are concerned for the future of mosquito control in NC.
Keywords: Environmental health; Public health; Entomology; Disaster assistance; Emergency management; Mosquito control; Mosquitoes--Control--North Carolina--Washington County; Mosquitoes--Control--North Carolina--Tyrrell County; Mosquitoes--Control--Finance; Hurricane Irene, 2011